Design of a Robust Decentralized Power System Stabilizer for Sudan National Grid - Hassan, Ibrahim; Romadan, Kamal; Hamuda, Elamin (University of Khartoum Engineering Journal, 2022)
Power system stabilizers (PSS) are used to generate supplementary control signals for the excitation system in order to damp the low frequency, generator angle, speed variation, generator power, voltage magnitude and power flow oscillations. This paper presents robust decentralized power system stabilizer (PSS) design approaches for a power system consisting of 41 machines with 167 buses. This paper mainly focuses on developing robust decentralized control techniques for power systems, with special emphasis on problems that can be expressed as minimizing a linear objective function under linear matrix inequalities [LMI] in tandem with bilinear matrix inequalities [BMI] constraints. The design problem is considered the natural extension of the reduced order for decentralized dynamic output H2/H∞ -norm controller’s synthesis for power systems. The resulting optimization problem has a general bilinear matrix inequalities (BMIs) form which can be solved using an iterative linear matrix inequalities [LMIs] programming method. Simulations were carried out using loss of line without fault tests at transmission line on Sudan grid.